Improvising Medicine : An African Oncology Ward in an Emerging Cancer Epidemic - Livingston, Julie (Book collections on Project MUSE., 2012)
"In Improvising Medicine, Julie Livingston tells the story of Botswana's only dedicated cancer ward, located in its capital city of Gaborone. This affecting ethnography follows patients, their relatives, and ward staff as a cancer epidemic emerged in Botswana"--Publisher's description.